The past, present, and future of endoscopic management for biliary strictures: technological innovations and stent advancements - Ni, Dong-jin; Yang, Qi-fan; Nie, Lu; Xu, Jian; He, Si-zhe; Yao, Jun (Frontiers in Medicine, 2024)
Biliary stricture can be induced by intrinsic narrowing and extrinsic compression, with the majority of cases being malignant. Clinically, distinguishing between benign and malignant biliary strictures remains a considerable challenge, and the ongoing disagreement over the optimal choice of biliary stents significantly influences treatment strategies and impacts patients' survival and prognosis. The utilization and advancement of endoscopic techniques have heightened the diagnostic sensitivity for biliary strictures. Concurrently, innovative technologies such as Endoscopic Ultrasound and Magnetic Compression Anastomosis emerge as viable alternatives when Endoscopic Retrograde Cholangiopancreatography (ERCP) is not an option, providing fresh insights for the clinical management of these patients.Traditional plastic and metal stents, characterized by their complex application and limited scope, have been unable to fully satisfy clinical needs. The introduction of novel stent varieties has notably improved this scenario, marking a considerable progression towards precision medicine. However, the clinical validation of the diverse stent materials available is incomplete. Hence, a thorough discussion on the present state and evolving trends of biliary stents is warranted.